Pengetahuan Perpajakan, Akuntabilitas Pelayanan Publik, Sanksi Perpajakan, Kesadaran Wajib Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi (KPP Pratama Mataram Barat) - Kadek Sindi Juniantara; Endang Kartini; Herawati Khotmi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2026)
This study aims to determine how the knowledge of taxation, accountability of public services, tax sanctions, and taxpayer awareness of the level of individual tax compliance at the KPP Pratama. This study uses a descriptive associative approach questionnaires are distributed to individual taxpayers at the IKPP Pratama. The number of samples is 100 registered. Multiple regression analysis is the method used in this study. The descriptive results of the study show that taxpayer knowledge, public service accountability, and tax sanctions do not significantly influence individual taxpayer compliance at the West Mataram Tax Office (KPP Pratama). Conversely, taxpayer awareness has a significant impact on individual taxpayer compliance at the West Mataram Tax Office (KPP Pratama).